Comparison of structured nutrition therapy for Ramadan with standard care in type 2 diabetes patients - Mohd Yusof, Barakatun Nisak; Wan Zukiman, Wan Zul Haikal Hafiz; Abu Zaid, Zalina; Omar, Noraida; Mukhtar, Firdaus; Yahya, Nor Farahain; Mohd Shahar, Aainaa Syarfa; Hasbullah, Farah Yasmin; Liu, Rachel Xin Yi; Marczewska, Agnieszka; Hamdy, Osama (MDPI, 2020)
(1) Background: Structured nutrition therapy (NT) is essential for the management of type 2 diabetes (T2D), but the optimal delivery during Ramadan fasting remains unclear. The present study aimed to evaluate the effect of structured NT program versus standard care in patients with T2D during Ramadan. (2) Methods: The present study was an 8-week, parallel, non-randomized study with patients’ preference design involving 64 patients with T2D. The participants were asked to choose their preferred group, i.e., structured NT (Structured Ramadan NT, sRNT) or standard care (SC). The participants in the sRNT group received a Ramadan-focused nutrition plan, including a diabetes-specific formula throughout the study, whereas the patients in the SC group received standard nutrition care. Study outcomes included clinical outcomes and quality of life (QoL). Data was analyzed using two-way repeated-measures ANOVA and linear mixed-effects model. (3) Results: More than half of the participants (n = 38, 63%) chose sRNT as their preferred group. Both groups had comparable baseline characteristics. After 8-weeks of the respective intervention, participants in the sRNT group had lower levels of fasting plasma glucose (−0.9 ± 0.3 mmol/L vs. 0.2 ± 0.3 mmol/L, p < 0.05), triglycerides (−0.21 ± 0.08 mmol/L vs. 0.20 ± 0.17 mmol/L, p < 0.05), and self-monitoring glucose at pre-dawn (6.9 mmol/L vs. 7.8 mmol/L, p < 0.05) and pre-bedtime (7.6 mmol/L vs. 8.6 mmol/L, p < 0.05) than participants in the SC group. Although not different between groups, HbA1c levels decreased significantly in the sRNT (−0.72 ± 0.16%, p < 0.001) but not in the SC group (−0.35 ± 0.24%, p = 0.155). QoL and satisfaction scores improved significantly in sRNT group, but not in SC group. (4) Conclusions: The structured NT regimen for Ramadan is a feasible and beneficial program for T2D patients observing Ramadan fasting as it showed an improvement in clinical outcomes and QoL.